l'art à l'hôpital en Europe : Brussel - Madrid - Paris. - Even, Rachel; Hôtel de Ville, Brussel; Comunidad de Madrid, Madrid (Parijs : Art dans la Cité, 2001)
Bailly, Virginie ; Claeye, Catherine ; de Lamo, Fran Arrojo ; Fernagu, Harald
Art in European Hospitals: Brussels, Madrid, Paris, Exhibition Halls of the Comunidad de Madrid, Madrid, june 6 - june 13, 2001
Art in European Hospitals: Brussels, Madrid, Paris, Parijs, september 2001
Art in European Hospitals: Brussels, Madrid, Paris, Hôtel de Ville, Brussel, july 4 to july 15, 2001
kunstcatalogus